Instructional supervision practices of cooperating teachers : basis for a handbook for student teacher supervision - Milanio, Rosario B. (Dagupan City, Pangasinan : [s.n.], 2016)
Utilizing the descriptive-survey design of research, the present study sought to determine the supervision practices of cooperating teachers as perceived by both student teachers and cooperating teachers themselves, the level of preparedness of cooperating teachers in supervising student teachers. The present study also looked into the relationship between cooperating teachers profile characteristics and approach to supervision. One hundred four cooperating teachers and eighty two student teachers served as respondents to this study, Data were gathered through direct administration of survey-questionnaires to the respondents. Tools for data analysis included the weighted mean, percentage, and chi-square test of independence.
Bibliography: pages 226-231.
CHED-La Union
Keywords: Student teaching